Afghanistan beyond the fog of war persistent failure of a rentier state - Fredholm, Michael (Nordic Institute of Asian Studies monograph series, 2018)
This is the first book to scrutinize the root causes of problems today with Afghan reconstruction. It begins in 1880 with the coming to power of Emir Abdur Rahman and departure of an occupying British army. On the northern border, Russian forces were also poised. Determined to preserve Afghan independence, Abdur Rahman devised a nation-building project grounded on centralized, autocratic rule and based on security, modernization and economic reform. Though continued by his successors, this project ultimately failed. A key reason for this was that, even as Abdur Rahman implemented policies that might be understood as 'Western' and 'rational', the great powers of the day took their cue from traditional institutional relationships in Afghanistan; local patronage relations were extended to the international level. In the process, Afghanistan became a rentier state, Abdur Rahman's model abandoned in favor of foreign subsidies increasingly diverted from security and economic development. Successive foreign powers, especially the Soviet Union and United States, have upheld this centralized, rentier model of governance and development despite it consistently failing over the years